Neurophysicological findings after anterior communicant artery aneurysm surgery (AcomA): a literature review - dos Santos, Camila B.; de Carvalho, Simone C.; Figueiredo, Eberval G.; Teixeira, Manoel J. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2011)
Objective: To present a literature review of cognitive disorders in patients operated on anterior communicant artery aneurysm (AcomA). Methods: Literature was searched (PubMed) from 1996 to 2009 using “aneurysm”, “surgery” and “neuropsychological evaluation” as keywords. Only papers describing postoperative neuropsychological findings were included in this review. Results: A great deal of the retrieved papers noted alterations of intellectual, executive functions and memory (episodic and semantic). Some authors explain these memory deficits as secondary to the executive dysfunction or ischemia in related areas. Other papers noted secondary alterations after temporary clipping (worse alert and selective attention). Majority of deficits improve with time, however, long periods of temporary clip are associated with persistent deficits. Conclusion: The studies are scarce in the Brazilian literature that valued thoroughly neuropsychological alterations after AcomA surgery, correlating data with the resection or not of the straight gyrus, with the presence or not of vasoespasm and alterations in the quality of life. There were not found, up to the moment, studies in which these patients were valued pre and post surgery.
Keywords: Cognitive deficit; aneurysm; anterior communicant artery